Vključevanje naravovarstvenih vsebin v programske dokumente izvajanja Skupne kmetijske politike v obdobju 2007 – 2027 - Žvikart, Mateja (Varstvo narave, 2025)
In this article, we provide an overview of the inclusion of nature conservation content in national programmes for the Common Agricultural Policy (CAP) for the period 2007-2027. We focus on three key areas of action: (1) Cross-compliance or Conditionality, (2) Eco-schemes (SOPO), and (3) Agrienvironment-climate payments (KOPOP). The review clearly shows that the number of environmental and climate interventions and content related to biodiversity conservation is increasing over the years, while at the same time the content is becoming more targeted. The regular and careful work of nature conservation professionals plays a key role in this. Furthermore, the Ministry of Agriculture, Forestry and Food has assumed an important coordinating and integrative role in facilitating cooperation among sectors, stakeholders, and experts throughout this process.
Keywords: biodiversity; biotska raznovrstnost; Common Agricultural Policy; cross-compliance; KOPOP; naravovarstvene vsebine; nature conservation content; navzkrižna skladnost; Program razvoja podeželja; Rural Development Program; Skupna kmetijska politika; SOPO; strategic Plan; strateški načrti